Evaluation of questionnaire-based information on previous physical work loads - Torgén, M.; Winkel, Jörgen; Alfredsson, Lars; Kilbom, Åsa; Stockholm MUSIC 1 Study, Group (Scandinavian Journal of Work, Environment & Health, 1999)
' ' OBJECTIVES ': 'The principal aim of the present study was to evaluate questionnaire-based information on past physical work loads (6-year recall).' ' METHODS ': 'Effects of memory difficulties on reproducibility were evaluated for 82 subjects by comparing previously reported results on current work loads (test-retest procedure) with the same items recalled 6 years later. Validity was assessed by comparing self-reports in 1995, regarding work loads in 1989, with worksite measurements performed in 1989.' ' RESULTS ': 'Six-year reproducibility, calculated as weighted kappa coefficients (kw), varied between 0.36 and 0.86, with the highest values for proportion of the workday spent sitting and for perceived general exertion and the lowest values for trunk and neck flexion. The six-year reproducibility results were similar to previously reported test-retest results for these items; this finding indicates that memory difficulties was a minor problem. The validity of the questionnaire responses, expressed as rank correlations (rs) between the questionnaire responses and workplace measurements, varied between -0.16 and 0.78. The highest values were obtained for the items sitting and repetitive work, and the lowest and "unacceptable" values were for head rotation and neck flexion. Misclassification of exposure did not appear to be differential with regard to musculoskeletal symptom status, as judged by the calculated risk estimates.' ' CONCLUSION ': 'The validity of some of these self-administered questionnaire items appears sufficient for a crude assessment of physical work loads in the past in epidemiologic studies of the general population with predominantly low levels of exposure.
Keywords: differential misclassification; exposure assessment; occupational exposure; questionnaire; reproducibility; retrospective study; validity